DAMPAK KETIDAKSESUAIAN JENIS PENUTUPAN LAHAN DENGAN KELAS KEMAMPUAN PENGGUNAAN LAHAN TERHADAP EROSI - Wahyuningrum, Nining; Sudira, Putu; Supriyo, Haryono; Sabarnudin, Sambas (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2015)
Land is a natural resource with a limited number so that the utilization of this resource should consider its ability to be able to produce sustainably. Inappropriate use may result in land degradation as indicated by the amount of erosion. This study aims to (1) evaluate the land use capability (LUC) classes and their conformity with the actual land use, (2) determine the impact of mismatches between the LUC classes and actual land use on erosion. Study was conducted in Tapan and Ngunut I Sub-Sub-watershed, Karanganyar District, Central Java. Universal Soil Loss Equation (USLE) was used to predict the potential erosion on the area while modified FAO method was used to analyze LUC. The results showed that the percentage of disagreement between LUC class and with actual land use in Tapan was 23% while in Ngunut was only 0.02%. The percentages of those disagreements have no effect on the magnitude of the annual erosion. Annual erosion in Tapan (15.12 tonnes / ha) is still smaller than in Ngunut I (25.63 tonnes / ha). Composition of land cover types and land management affect the amount of erosion. Cultivation of crops at dry land and land tillage during growing season in accordance with the rainy season has great contribution on erosion. Keywords : Unsuitability, land covers, LUC, erosion